2021
DOI: 10.1007/s10815-021-02265-3
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the link between phthalate exposure and endometriosis in humans: a systematic review and meta-analysis of the literature

Abstract: Purpose Endometriosis is a chronic debilitating inflammatory pathology which interests females in their reproductive age. Its pathogenesis has not yet been clearly defined. Recent evidence linked chemical agents as endocrine-disrupting chemicals to endometriosis. Phthalates are a widely used class of such compounds. This study aimed to summarize the current literature evaluating the link between exposure to phthalates and occurrence of endometriosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…Our findings are consistent with those of the previous studies [21], [22]. However, our findings are not in agreement with another previous study that has not discovered a significant connection between DEHP levels and endometriosis (p = 0.161), but a statistically significant weak association between MEHP levels and endometriosis (p = 0.020) in their case-control study [23].…”
Section: Discussionsupporting
confidence: 72%
“…Our findings are consistent with those of the previous studies [21], [22]. However, our findings are not in agreement with another previous study that has not discovered a significant connection between DEHP levels and endometriosis (p = 0.161), but a statistically significant weak association between MEHP levels and endometriosis (p = 0.020) in their case-control study [23].…”
Section: Discussionsupporting
confidence: 72%
“…In the case of endometriosis, a significant increase in the risk of develop endometriosis has been estimated in women with higher DEHP exposure (OR = 1.42; 95% CI: 1.19–1.70) [ 10 ]. In addition, in other studies, higher levels of both the parental compound and its metabolites (MEHP, MEHHP, and MEOHP) have been detected in the plasma, serum, peritoneal fluid, and urine of women with endometriosis compared with healthy controls [ 5 , 11 , 12 , 13 , 14 , 15 , 16 ]. One of the mechanisms that could explain the relationship between DEHP exposure and an increased risk of endometriosis could be the induction of the above-mentioned molecular abnormalities in the eutopic endometrium of women with endometriosis.…”
Section: Introductionmentioning
confidence: 89%
“…Endocrine disrupting chemicals (EDCs) interfere with hormonal and immunological signaling and alter the epigenetics of target cells [ 3 , 4 ]. Specifically, a link between phthalate exposure and the risk of endometriosis has been described in several population-based case-control studies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Huan et al found that exposure to PAEs, especially DEHP, was associated with the occurrence of endometriosis ( Yi et al, 2023 ). In a meta-analysis, Conforti et al found that endometriosis was associated with increased urinary levels of MBP/MnBP, MEOHP, and MEHHP, but not for others ( Conforti et al, 2021 ).…”
Section: Reproductive Toxicity Of Phthalic Acid Estersmentioning
confidence: 99%